Protective effect of miR-33-5p on the M1/M2 polarization of microglia and the underlying mechanism. Issue 4 (1st April 2022) - Chai, Song; Sheng, Yilan; Sun, Ran; He, Jieshi; Chen, Lihua; He, Fei; Chen, Wenhua; Ma, Dingying; Yu, Bo
ABSTRACT: This study was aimed to investigate the influence of miR-33-5p on the M1/M2 polarization of microglia and the underlying mechanism. Transcriptome sequencing was performed using microglia from miR-33-5p mimic and control groups. In total, 507 differentially expressed genes, including 314 upregulated genes and 193 downregulated genes, were identified. The subnetwork of module A, which was extracted from the protein–protein interaction networks, mainly contained the downregulated genes. Cdk1, Ccnb, and Cdc20, the members of module-A networks with the highest degrees, possess the potential of being biomarkers of ischemic stroke due to their function in the cell cycle. NFY, a transcription factor, was predicted to have the regulatory relation with nine downregulated genes. Overall, our findings will provide a valuable foundation for genetic mechanisms and treatment studies of ischemic stroke. Graphic abstract: uf0001